Greener than Others? Exploring Generational Differences in Green Purchase Intent. (May 2022) - Ham, Chang-Dae; Chung, Un Chae; Kim, Woo Jin; Lee, Seo Yoon; Oh, Sang-Hwa
This study explored the generation gap in American consumers' green perceptions and purchase intentions across four generations (Gen Z, Y, X, and Baby Boomers) from the perspectives of consumer socialization and social intelligence. Analyzing a nationally representative sample of adults in the United States ( N = 19, 450), the survey results revealed that the American consumer's green norms and beliefs varied by generation. A series of multiple regression analyses showed that each generation had similar but idiosyncratic beliefs in purchasing products from green companies. Theoretical and practical implications are discussed.